Ex Vivo Evaluation of Carpal Flexion After Partial Carpal Arthrodesis in Horses. Issue 3 (25th October 2014) - Tulloch, Patty J.; Johnston, James D.; Barber, Spencer M.; Gellert, Candace L.; Lang, Hayley M.; Panizzi, Luca
<x xml:space="preserve">Abstract</x> Objective To determine degrees of flexion after arthrodesis of the antebrachiocarpal (ABC) joint, middle carpal (MC), and carpometacarpal (CMC) joints combined (MC/CMC), and carpometacarpal (CMC) joint alone. Study Design Ex vivo study. Animals Forelimbs (n = 9) from 2‐ to 10‐year‐old Quarter Horses (5), Thoroughbred (2), and American Paint Horse (2). Methods Using 2 locking compression plates, 3 partial carpal arthrodesis techniques were performed. Cables and deadweights were connected to limbs and each angle of flexion determined 3 times using a protractor and then averaged. Control measurements were obtained before and after arthrodesis, the techniques randomized with Latin square design. Descriptive data were analyzed with Levene's test, Q‐Q plots, ANOVA, and Bonferroni test. Results Mean ± SD carpal flexion results were: controls 150° ± 8°, CMC arthrodesis 149° ± 9°, MC/CMC arthrodesis 43° ± 7.6°, and ABC arthrodesis 25° ± 6.3°. There was no significant reduction in flexion after a CMC arthrodesis compared with controls (P = .21), but there was after ABC (P < .001) and MC/CMC arthrodesis (P < .001), with the ABC arthrodesis significantly reduced compared with an MC/CMC arthrodesis (P < .001). Conclusions Whereas CMC arthrodesis does not affect carpal flexion, CMC/MC and ABC arthrodesis markedly reduce the degree of carpal flexion.